Moderate to Intense Physical Activity Is Associated With Improved Clinical, CD4/CD8 Ratio, and Immune Activation Status in HIV-Infected Patients on ART. (28th December 2021) - Bernal, Enrique; Martinez, Monica; Campillo, José Antonio; Puche, Gabriel; Baguena, Carlos; Tomás, Cristina; Jimeno, Amaya; Alcaraz, Maria Jose; Alcaraz, Antonia; Muñoz, Angeles; Oliver, Eva; de la Torre, Alejandro; et al.
Abstract: Background: Physical activity has anti-inflammatory effects and reduces morbidity and mortality in the general population, but its role in the clinical, CD4/CD8 ratio, and immune activation status of HIV-infected patients has been poorly studied. Methods: A cross-sectional study was carried out in a cohort of 155 HIV-infected patients on stable antiretroviral therapy (ART) to compare clinical, biochemical, CD4/CD8 ratio, and immune activation status according to their physical activity in the last 2 years (sedentary/low vs moderate/intense) assessed by the iPAQ. A binary logistic regression and mixed analysis of variance were performed to evaluate the impact of levels of physical activity on CD4/CD8 ratio. Results: In our series, 77 (49.7%) out of 155 patients were sedentary, and 78 (50.3%) practiced moderate/intense physical activity. Moderate/intense physical activity was associated with better metabolic control (lower body mass index, P  = .024; glucose, P  = .024; and triglyceride, P  = .002) and CDC HIV stage ( P  = .046), lower CD8 + ( P  =  .018), CD4 + CD8 + ( P  = .026), CD4 + CD86 + ( P  = .045), CD4 + HLA-DR + ( P  = .011), CD8 + HLA-DR + ( P  = .048) T lymphocytes and CD16 + HLA-DR + natural killer cells ( P  = .026), and higher CD3 + CD4 + T lymphocytes ( P  = .016) and CD4/CD8 ratio ( P  = .001). Sedentary lifestyle (odds ratio [OR],  2.12; P  = .042), CD4 nadir (OR,  1.005; P  < .001), and CD8 + CD38 + T cells (OR,  1.27; P  = .006) were independently associated with low CD4/CD8 ratio (<0.8). Earlier and more intense CD4/CD8 ratio recovery was observed in patients with higher physical activity in the 2-year follow-up with a significant interaction between these variables: F(2, 124) = 3.31; P  = .049; partial η2 = 0.042. Conclusions: Moderate to high physical activity is associated with beneficial health effects, improvement in metabolic profile, and reduction of chronic inflammation in patients with HIV. Although more studies and clinical trials are needed to confirm these findings, a healthy lifestyle including at least moderate physical activity should be recommended to HIV patients on stable ART.